Policing literary theory - Mihailescu, Calin Andrei, 1956-; Yokota, Jeri, 1959- (Text (Rodopi (Firm)), 2018)
The present age of omnipresent terrorism is also an era of ever-expanding policing. What is the meaning -- and the consequences -- of this situation for literature and literary criticism? Policing Literary Theory attempts to answer these questions presenting intriguing and critical analyses of the interplays between police/policing and literature/literary criticism in a variety of linguistic milieus and literary traditions: American, English, French, German, Japanese, Korean, Russian, and others. The volume explores the mechanisms of formulation of knowledge about literature, theory, or culture in general in the post-Foucauldian surveillance society. Topics include North Korean dictatorship, spy narratives, censorship in literature and scholarship, Russian and Soviet authoritarianism, Eastern European cultures during communism, and Kafka's work. Contributors: Vladimir Biti, Reingard Nethersole, Călin-Andrei Mihăilescu, Sowon Park, Marko Juvan, Kyohei Norimatsu, Péter Hajdu, Norio Sakanaka, John Zilcosky, Yvonne Howell, and Takayuki Yokota-Murakami.